If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1) = 3 Reorder the terms: (-1 + 2x) = 3 Remove parenthesis around (-1 + 2x) -1 + 2x = 3 Solving -1 + 2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 3 + 1 2x = 3 + 1 Combine like terms: 3 + 1 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| z+3/z-7=8/-3 | | -15=2x+3x | | .75=2x+9 | | 95-5x=22x+23 | | 2x+9=1.5 | | x-17=1-2 | | -55-9=9x+17 | | X^2-96x+256=0 | | x-11=9-10 | | d-6=7 | | x+6+x+9+x+3=x+1+x+1+x+4+x+4 | | 1.5b(3)=36 | | x/4+x/12=8 | | -8+4=x+6 | | -1/2x=23 | | y=17x^2+23x+19 | | -9-7=x-2 | | -5(-9z+13)=7(5z+19)-8 | | 9x-4=2x+78 | | 19g=-2(-4g-11) | | (1/16x^-8)^-1 | | -6(-9w-5)=-4(-12w-18) | | 75+39.95x=39.95x | | -6(4f-20)+15=-9f | | -20+2(14b-13)=-2(-9b-17) | | d/2=10 | | 8(r-11)=-9+2r+5 | | -7=k+7 | | i^2+i^3= | | 2+6(5+y)-4=92 | | -9=h/3 | | 2x^5=5x^4 |